Deletion analysis of the Ure2p in Saccharomyces cerevisiae and effect of NCR on the production of ethyl carbamate during wine fermentations - Erasmus, Daniel J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2000.